Analysis of International Expert Migration: A Case Study of Brain Drain in the Philippines in 2015-2023 - Pratama Angelita, Pristian; Laksmi Perbawani, Firsty Chintya (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Filipina telah menjadi negara yang aktif mengirim pekerja ke seluruh dunia sejak era 1970-an, terutama para pekerja tenaga ahli. Tingginya tingkat migrasi tenaga ahli di Filipina didorong oleh budaya masyarakat yang percaya bahwa bekerja di luar negeri dapat meningkatkan kualitas hidup mereka. Namun, fenomena ini telah menimbulkan masalah internal, yakni munculnya fenomena brain drain. Brain drain dipicu oleh faktor penarik dan faktor pendorong. Faktor-faktor tersebut dapat dianalisis lebih lanjut melalui keterkaitannya dengan wilayah asal, wilayah destinasi, hambatan yang mengintervensi, dan faktor personal. Penelitian ini bertujuan untuk menganalisis fenomena migrasi internasional tenaga ahli dan dampak brain drain di Filipina tahun 2015 hingga 2023 menggunakan push-pull factors. Penulis menggunakan pendekatan deskriptif kualitatif untuk mendeskripsikan fenomena yang terjadi. Metode pengumpulan data yang digunakan termasuk wawancara dan studi literatur. Hasil penelitian ini menggambarkan hubungan yang erat antara migrasi internasional di Filipina dan fenomena brain drain yang berdampak pada sektor-sektor penting seperti ekonomi, politik, dan sosial-budaya Filipina. Analysis of International Expert Migration: A Case Study of Brain Drain in the Philippines in 2015-2023 Abstract: The Philippines has actively sent workers around the world since the 1970s, particularly highly skilled workers. The Philippines' high level of skilled migration has been driven by a culture in which people assume that working abroad will improve their standard of living. However, this trend ended up resulting in internal difficulties, including the rise of the brain drain phenomenon. Brain drain is caused by both pull and push causes. These elements can be examined further in relation to the place of origin, destination region, intervening obstacles, and personal factors. The purpose of this study is to examine the phenomenon of international highly skilled migration and the impact of brain drain in the Philippines between 2015 and 2023 utilizing push-pull factors. The author employs a qualitative descriptive approach to describe the phenomena that occur. Interviews and literature reviews were employed as data-gathering strategies. The findings of this study demonstrate the significant correlation between international migration in the Philippines and the brain drain issue, which has consequences for key areas such as the Philippine economy, politics, and sociocultural. Keywords: Brain Drain, International Highly Skilled Migration, Migration.